2016
DOI: 10.1126/science.aaf7012
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal coordination of stem cell commitment during epidermal homeostasis

Abstract: Adult tissues replace lost cells via pools of stem cells. However, the mechanisms of cell self-renewal, commitment, and functional integration into the tissue remain unsolved. Using imaging techniques in live mice, we captured the lifetime of individual cells in the ear and paw epidermis. Our data suggest that epidermal stem cells have equal potential to either divide or directly differentiate. Tracking stem cells over multiple generations reveals that cell behavior is not coordinated between generations. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
230
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(257 citation statements)
references
References 31 publications
18
230
0
Order By: Relevance
“…Conversely, 1 study found no evidence of slow-cycling epithelial stem cells in the mouse esophagus, and suggested that each cell within the basal cell layer is equipotent in generating both proliferating and differentiating cells with equal probability (10). This equipotent model has also been reported for the stratified epithelium of the skin (16).…”
Section: Krt15-crepr1 R26mentioning
confidence: 88%
“…Conversely, 1 study found no evidence of slow-cycling epithelial stem cells in the mouse esophagus, and suggested that each cell within the basal cell layer is equipotent in generating both proliferating and differentiating cells with equal probability (10). This equipotent model has also been reported for the stratified epithelium of the skin (16).…”
Section: Krt15-crepr1 R26mentioning
confidence: 88%
“…These observations have led to a model of epidermal stem cell function that is distinct from those previously postulated (Rompolas et al, 2016).…”
mentioning
confidence: 95%
“…and marked cells within the epidermis has recently revealed that epidermal stem cells have equal potential to either divide or directly differentiate, a process seemingly coordinated by the fate of sibling cells (Rompolas et al, 2016). These observations have led to a model of epidermal stem cell function that is distinct from those previously postulated (Rompolas et al, 2016).…”
mentioning
confidence: 98%
See 2 more Smart Citations